Expression of TGF-β in malignant transformation of oral lichen planus - A systematic review - Harinisubasri M; Priyadharsini Nataraj; Dineshkumar Thayalan; Divya Bose; Rameshkumar Annasamy; Rajkumar K (Oral Oncology Reports)
Background: Malignant potential of Oral Lichen Planus (OLP) is underestimated and given less importance. Only few studies were noted explaining the pathogenesis involved in its cancer progression. Aim: The aim of the study is to bring in a spotlight for masquerading the role of TGF-β by determining its expression using immunohistochemistry in the malignant transformation of oral lichen planus. Materials and methods: This systematic review followed PRISMA guidelines and criteria. Electronic literature searches were carried out in databases MEDLINE (via PubMed) and Google Scholar to identify studies that matched the following MESH Terms (Expression AND TGF-β AND oral lichen planus) for identifying articles published between 2008 t0 2021. Manually searched for the references and citations of the identified articles for further research studies. Results: All the articles included in this study included TGF-β and its related protein expression in both its pathogenesis and cancer growth.This help to bring in newer and targeted treated options. Conclusion: Role of TGF in lichen planus was briefly studied and it was concluded that TGF-β played a major role in its malignant transformation. To discover the role TGFβ in the maintenance of chronic tonicity of the disease and thereby unmasking its function in malignant transformation of OLP a systematic review is done. This systematic review accumulates all the possible effects of TGF-β in malignant transformation of oral lichen planus. So thereby it helps in developing novel targeted therapy to shield the lesion from its carcinomatous transformation.